2012
DOI: 10.1177/0218492311435339
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of open heart surgery in patients with liver cirrhosis

Abstract: Open heart surgery in patients with liver cirrhosis is considered to be very risky, but the predictors of poor outcomes in such cases have not been established. We report the perioperative results of open heart surgery in patients with liver cirrhosis in our hospital. We reviewed the results of 13 cases in 12 patients with liver cirrhosis who underwent open heart surgery between January 2001 and December 2010. The Child-Turcotte-Pugh classification, the model for end-stage liver disease score, EuroSCORE, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…Complications in CABG with LD were greater than in the NLD cohort (OR = 1.73; 95% CI = 1.46–2.05) and in VS with LD (OR = 2.77; 95%, CI 2.13–3.60). This is consistent with other reports in the literature reporting higher complication rates [ 7 , 8 ]. Modi et al reported complications rates in a graded fashion with increasing severity of LD in the range of 20–60% with CP class A, and 50–100% with CP class B and C. The highest overall complication rates were reported by Hayashida et al, at 25–50%, 100%, and 100% with CP class A, B, and C, respectively.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Complications in CABG with LD were greater than in the NLD cohort (OR = 1.73; 95% CI = 1.46–2.05) and in VS with LD (OR = 2.77; 95%, CI 2.13–3.60). This is consistent with other reports in the literature reporting higher complication rates [ 7 , 8 ]. Modi et al reported complications rates in a graded fashion with increasing severity of LD in the range of 20–60% with CP class A, and 50–100% with CP class B and C. The highest overall complication rates were reported by Hayashida et al, at 25–50%, 100%, and 100% with CP class A, B, and C, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…In patients with combined CP class B and C, major morbidity is conservatively estimated at 50–100% [ 9 ]. Acute kidney injury requiring dialysis, increased bleeding leading to increased transfusion requirements, increased incidence of infections and pulmonary issues are amongst the most frequently cited complications [ 5 , 7 , 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Morisaki et al [19] in their study showed that a good cutoff value for predicting postoperative morbidity was a platelet count of less than 9.6×10 4 /μl and indicates the presence of advanced liver fibrosis or cirrhosis while Amal et al [17] demonstrated 15.0×10 4 /μl and this cutoff value did not indicate advanced liver fibrosis or cirrhosis. However, other studies reported no difference in platelet count between the groups [39]. In the current study, preoperative platelet count was comparable to other studies with no differences between the two studied groups (16.05±7.77×10 4 /μl and 15.95±6.19×10 4 /μl for group (I) and (II) respectively), but group (II) showed statistically significant difference as regards postoperative need for platelet transfusion (41.66% compared to 25.92% in group (I)) which again confirms that prolonged operative time and CPB time deplete platelets more.…”
Section: Discussionmentioning
confidence: 84%
“…Other studies showed comparable postoperative results to ours where Arif et al [38] and Thielmann et al [31] in their separate studies showed that renal complications were the postoperative complications. Another report by Sugimura et al [39] showed that hepatic complications were the main postoperative complications. The studies reported by Amal et al [17] and Hsieh et al [30] showed that cardiac complications were the main postoperative complications and the same result was obtained by Lopez-Delgado et al [40].…”
Section: Discussionmentioning
confidence: 95%
“…Early reports suggest a mortality of 30–40% and morbidity of up to 70–100% . Studies have consistently shown a proportionately high mortality and morbidity (including but not limited to: ascites, cardiac tamponade, pleural effusion, bleeding and encephalopathy) with worsening Child and MELD classification in patients undergoing CABG prior to liver transplantation . A ‘cut‐off’ Child score >7 was found to have a sensitivity and specificity of 86% and 92%, respectively for mortality with a PPV and NPV of 67% and 97%, respectively in some studies.…”
Section: Profiles Of Cardiac Dysfunction In End‐stage Liver Diseasementioning
confidence: 98%